Factors Associated with Persistence of Malaria Prevalence Among Under Five Children in Maiha Local Government Area, Adamawa State, Nigeria - Mohammed, Chidama Ibrahim; Kirchinga, Chinda Ndumari; Idris, Aliyu; Girei, Mohammed Hayatu (Darul Yasin Al Sys, 2025)
The research determined the factors associated with persistence of malaria prevalence among UN5 in Maiha Local Government Area, Adamawa State, Nigeria. Consecutive sampling method was employed to enroll a total of 2822 UN5 who attended the sampled health facilities from 19th September, 2024 to 31st October, 2024. These UN5 were subjected to malaria diagnostic tests using both mRTD and microscopy. The caregivers of these UN5 were interviewed using a structured questionnaire for data collection on factors influencing the persistence of malaria among UN5. Data collected was analyzed using descriptive and logistic regression model for the prevalence of malaria. mRTD and microscopy results revealed malaria prevalence of 76.47% (2158). Logistic regression result on demographic factors was (R2 = 0.6849) with Age of the child, Marital Status of caregiver, Educational Qualifications of caregiver, Income of caregiver and Occupations of caregiver all had positive coefficient and were all significant at 1%. The contributory Environmental factors was (R2 =, 0.5533), and its components were drainage pattern, Bushes around houses and garbage heaps were all significant at 1% as a factor influencing persistence of malaria. Care giver factors influencing malaria was (R2 =0.6826) This disclosed that care givers knew that mosquito bite causes malaria and high body temperature was a symptom of malaria as logistic regression results shows positive and is significant at 1%. Similarly, care givers in the study area don’t often use mosquito net as the result revealed shows positive coefficient. Similarly, the house hold factors has (R2 = 0.7681) having all the four household factors that are captured in this study which are the nature of houses,, time for going to bed, source of light and diet, all had positive coefficient and were significant at 1%.. Recommendations was made for a well-planned and resourced health education and promotion interventions by the government and other concerned malaria prevention organizations that focus on prevention and treatment of malaria burden amongst UN5 in Maiha local government area of Adamawa state, Nigeria.